Peningkatan Hasil Belajar Ilmu Pengetahuan Sosial melalui Pembelajaran Role Playing dengan Flanel Cerita - Tia Kristanti; Hermahayu Hermahayu; Ahmad Syarif (Universitas Muhammadiyah Magelang, 2019)
This study aims to determine the increase of Social Science achievement through Role Playing assisted with Story Flannel. It is a Classroom Action Research. The subjects are 30 fifth grade students of SDN Cacaban 1 of Magelang City. There are two cycles consisting of three meetings in each. Data are obtained through observation and tests. While they are analyzed through quantitative descriptive method. Pre-action test result reveals the average score is 53.63 with classical completeness 23.33%. The average score of Cycle I test is 66.73 with 66.33% of classical completeness. While in Cycle II, the average score is 78 with 93.33% of classical completeness. Hence, it can be concluded that Role Playing assisted with story flannel can improve student achievement in Social Sciences.